Social change in medieval Iran 132-628 AH (750-1231 AD) : the perspectives of Persian historiography - Kamālī, Maryam (Amsterdam University Press, 2023)
This study contributes to the history of social changes in Iran during the Abbasid Caliphate (AH 132-656, AD 750-1258) by foregrounding the perspective of Persian language historians - from Abu Ali Bal'ami (AH 363, AD 974), the first known Persian historian, to Atamelak Joveyni (AH 623-681, AD 1226-1283), the great historian of the Mongol Era. By applying the insights of Anthony Giddens and the theory of structuration to address the interactions of social agents and structures, this book provides a coherent narrative of social transformation in medieval Iran.